Child care in action infant & todler - Hoffman, Sara McCormack ([s.l.] : Thomson Delmar Learning, 2005)
Provides information specific to infant and foddler care , development and program management
System requirement ; Windows Pentium computer drive ; Windows 98/2000/XP/2003 ; CD-ROM drive ; Acrobat Reader ; Macromedia Flash Player
Keywords: Child care; Infants -- Care; Foddlers -- care; Child development